INTEGRASI NASIONAL DI ERA GLOBALISASI: TANTANGAN MULTIKULTURALISME DAN UPAYA PEMUDA INDONESIA - M Raisah Firdaus; Erin Aulidia; Widya Gupita Ayu Rizky; Nazlia Intania; Fani Herdiana; Rifki Ahmad Fauzan; Bambang Yuniarto (CV. ADIBA AISHA AMIRA, 2025)
This study analyses the challenges of national integration in Indonesia in the era of globalisation, which is characterised by the influence of foreign cultures, the identity crisis among the younger generation, horizontal conflicts based on ethnicity, religion, race and intergroup relations (SARA), as well as polarisation due to social media and economic disparities between regions, where multiculturalism with more than 1,340 ethnic groups becomes both a potential and a vulnerability for national unity. A comprehensive literature review shows that Indonesian youth play a strategic role as agents of change through efforts such as multicultural education, the #BersatuDalamBhineka digital campaign, participation in the KNPI organisation, inclusive cultural festivals, and cross-ethnic social advocacy, all of which strengthen the values of Pancasila and Bhinneka Tunggal Ika amid globalisation. The main findings emphasise the need for a holistic youth-based strategy to transform multicultural challenges into national strengths, with recommendations to strengthen digital literacy, intercultural dialogue, and inclusive policies to realise a united and resilient Indonesia Emas 2045